False Positive Findings on I-131 WBS and SPECT/CT in Patients with History of Thyroid Cancer: Case Series. (26th January 2017) - Hannoush, Zeina C.; Palacios, Juan D.; Kuker, Russ A.; Casula, Sabina
Abstract : Introduction. Although whole body scan (WBS) with I-131 is a highly sensitive tool for detecting normal thyroid tissue and metastasis of differentiated thyroid cancer (DTC), it is not specific. Additional information, provided by single photon emission computed tomography combined with X-ray computed tomography (SPECT/CT) and by the serum thyroglobulin level, is extremely useful for the interpretation of findings. Case Presentation. We report four cases of false positive WBS in patients with DTC: ovarian uptake corresponding to an endometrioma, scrotal uptake due to a spermatocele, rib-cage uptake due to an old fracture, and hepatic and renal uptake secondary to a granuloma and simple cyst, respectively. Conclusions. Trapping, organification, and storage of iodine are more prominent in thyroid tissue but not specific. Physiologic sodium-iodine symporter expression in other tissues explains some, but not all, of the WBS false positive cases. Other proposed etiologies are accumulation of radioiodine in inflamed organs, metabolism of radiodinated thyroid hormone, presence of radioiodine in body fluids, and contamination. In our cases nonthyroidal pathologies were suspected since the imaging findings were not corroborated by an elevated thyroglobulin level, which is considered a reliable tumor marker for most well-differentiated thyroid cancers. Clinicians should be aware of the potential pitfalls of WBS in DTC to avoid incorrect management.